Assessment on the average participation versus bialek’s methods for transmission pricing methodologies - Md Datar, Nurul Haziqah (2019)
Nowadays, the global trend especially in developing countries namely, Australia, New Zealand and Singapore and some countries are at various stages of developing a national electricity market has put pressure and force Malaysia to restructure electricity industry to be more reliable, effectively, transparent, efficient and sustainable. Currently, electricity supply industries do not provide an efficient services as competitive firms. Therefore, electrical industries in Malaysia need to move from a predominantly government owned and managed market to a more competitive and commercial one. One of the important issues in this restructuring market is the transmission pricing. The regulation of the transmission pricing is important in order to identify whether the transmission service system is economically beneficial to both side of users and utilities. In this research, 3 bus system and IEEE 6 bus system were used as case studies in order to determine the best method either the Average Participation or Bialek’s methods that reflects fair and equitable transmission pricing methodologies. Using Average participation method, the each of the transmission line has the power contribution from each user which follows the nature of power injection. Meanwhile, by using Bialek’s method the power contribution of each user to each line is not uniform since there are transmission lines that indicate no power injection from generators and loads. This will affect the allocation of charges for locational and non-locational components. Hence, from this research work, it can be concluded that the Average Participation method reflects an efficient transmission network as the charges is allocated based on the actual usage of the transmission user to the lines.